13. EVALUATE SURGICAL SAFETY FOR PATIENTS AT AGRICULTURE GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: Assess the level of surgical safety for patients at General Hospital of Agricultural in 2023 according to Decision No. 7482/QD-BYT of the Ministry of Health.Research subjects and methods: Cross-sectional descriptive study conducted on cases operated from April to September 2023.Results: Among the 147 patients who underwent surgery, with an average age of 44.1 ± 20.3 years (ranging from 2 to 86 years old). Of these surgeries, 138 (93.9%) were routine procedures, while 9 (6.1%) were emergency surgeries, laparoscopic surgery was performed on 86 patients (58.5%), and open surgery on 61 patients (41.5%). The total score for the evaluated criteria was 87.6 out of 110 points, with each criterion achieving a partial pass. Assessing the general surgical safety level at Agriculture General Hospital, the level of surgical safety is guaranteed.Conclusion: The Agriculture General Hospital has rigorously applied the quality criteria set by the Ministry of Health to assess the level of surgical safety, aiming to minimize medical incidents for patients. Assessing the general surgical safety level at Agriculture General Hospital, the level of surgical safety is guaranteed.
Keywords: Surgical safety